Through-the-scope suture closure of peroral endoscopic myotomy mucosal incision sites - Zhang, Linda Yun; Bejjani, Michael; Ghandour, Bachir; Khashab, Mouen A. (Endoscopy, 2022)
Background Peroral endoscopic myotomy (POEM) is now widely used for esophageal motility disorders including achalasia. Closure of the mucosal incision site is a critical step of the procedure. We evaluated the use of a novel through-the-scope (TTS) suture system for closure of POEM mucosal incision sites.Methods We retrospectively reviewed consecutive patients who underwent POEM with TTS suture closure at our institution between February and July 2021. Technical success was defined as complete mucosal incision site closure using TTS suturing, without the need for adjunctive devices. Continuous variables are presented as median (interquartile range [IQR]) or mean (SD).Results 35 consecutive patients (median age 58 years [IQR 46.5–72]; 54.3 % female) underwent POEM with attempted mucosal closure by TTS suturing. Technical success was achieved in 32 patients (91.4 %) with a mean closure time of 12.4 (SD 6.9) minutes. The median mucosal incision length at time of closure was 2.5 cm (IQR 2–2.5). Overall, 17 patients (53.1 %) required ≥ 2 TTS suture systems and 3 patients (8.6 %) required additional TTS clips to achieve secure mucosal closure. No adverse events were encountered.Conclusions TTS suturing was effective and safe for POEM mucosotomy closure. However, prospective comparative trials and cost-effectiveness analyses are warranted before routine adoption.